The sooner, the better: ROS, kinases and nutrients at the onset of the damage response in Drosophila - Serras, Florenci (Frontiers in Cell and Developmental Biology, 2022)
One of the main topics in regeneration biology is the nature of the early signals that trigger the damage response. Recent advances in Drosophila point to the MAP3 kinase Ask1 as a molecular hub that integrates several signals at the onset of regeneration. It has been discovered that reactive oxygen species (ROS) produced in damaged imaginal discs and gut epithelia will activate the MAP3 kinase Ask1. Severely damaged and apoptotic cells produce an enormous amount of ROS, which ensures their elimination by activating Ask1 and in turn the pro-apoptotic function of JNK. However, this creates an oxidative stress environment with beneficial effects that is sensed by neighboring healthy cells. This environment, in addition to the Pi3K/Akt nutrient sensing pathway, can be integrated into Ask1 to launch regeneration. Ultimately the activity of Ask1 depends on these and other inputs and modulates its signaling to achieve moderate levels of p38 and low JNK signaling and thus promote survival and regeneration. This model based on the dual function of Ask1 for early response to damage is discussed here.